Lymphoepithelioma-Like Carcinoma of the Salivary Gland: Is Radiotherapy Alone Adequate?. (2nd November 2011) - Kaidar-Person, Orit; Kuten, Abraham; Billan, Salem
Abstract : Introduction . Lymphoepithelioma-like carcinoma (LELC) of the salivary gland is a rare tumor. Currently, surgery with or without radiotherapy is the recommended treatment for all salivary gland carcinomas. However, in contrast to other high-grade salivary gland carcinomas, LELCs are considered radiosensitive. There are only a few published reports of radiotherapy alone for the treatment of salivary gland LELC. Case . We present two cases of LELC of the salivary gland. One was treated with surgery and postoperative radiotherapy, and the other was given a single cycle of chemotherapy and then radiotherapy. Currently, both patients have no evidence of disease. Conclusion . Radiotherapy as a single modality should be reevaluated. The role of systemic chemotherapy to gain systemic control should be addressed due to noteworthy metastatic disease.